Analysis of bitter orange dietary supplements for natural and synthetic phenethylamines by LC–MS/MS. Issue 9 (28th June 2020) - Pawar, Rahul S.; Sagi, Satyanarayanaraju; Leontyev, Dmitry
Abstract: Citrus aurantium, commonly known as bitter orange, is a popular dietary supplement ingredient sold worldwide. Bitter orange supplements are sold primarily as weight management and sports performance products and have gained popularity after Ephedra products were banned from the US market. Supplements containing synephrine are reported to exhibit adverse cardiovascular effects especially in the presence of caffeine. In this study, an LC–MS/MS method was established to quantify five natural amines (synephrine, octopamine, tyramine, N ‐methyltyramine, and hordenine) and four synthetic phenethylamines (phenylephrine, methylsynephrine, etilefrine, and isopropyloctopamine) in dietary supplements sold in the US. The method was validated and found to have acceptable performance to accurately measure analytes in complex botanical products. The average recoveries from a blank matrix were 88–125% with an RSD of 0.5–7.0%. Fifty‐nine products labeled to contain bitter orange peel, extract, or its amines were purchased and their amine content was measured. Several products were found to contain higher amounts of amines than that expected from a typical bitter orange extract. Of the 23 products that made label claims for synephrine, only 5 products (22%) were within 80–120% of labeled synephrine content. The presence of synthetic amines, methylsynephrine (up to 240 mg/daily serving), and isopropyloctopamine (up to 76 mg/daily serving), whose effects in humans are not known, were detected in six products and one product, respectively. While the use of methylsynephrine and isopropyloctopamine are not permitted in dietary supplements, hordenine, N ‐methyltyramine, and octopamine are currently listed on the FDA's Dietary Supplement Ingredient Advisory List. Abstract : An LC‐MS/MS method was developed and validated for the analysis of nine phenethylamines. The method was used to analyze 59 products sold as dietary supplements and labeled to contain bitter orange peel, extract, or its amines.